STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH DI SMP NEGERI 15 IT KOTA BINJAI - Dayati, Sri; Roslina, Roslina; Fajar, Rahmat (STKIP Pesisir Selatan, 2026)
School quality improvement is the main demand in dynamic and complex education management, so it requires principal leadership that is able to encourage sustainable change. Transformational leadership is considered relevant because it emphasizes vision, exemplary, motivation, and empowerment of all school members. This study aims to analyze the principal's transformational leadership strategy in improving school quality at SMP Negeri 15 IT Binjai City. The research method used is qualitative research with descriptive research type. Data were collected through interviews, observations, and documentation studies, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the principal implemented transformational leadership strategies through the formulation of a clear vision and mission, empowering teachers and education personnel, strengthening collaborative work culture, and increasing academic and managerial supervision. The strategy had a positive impact on improving teacher performance, a conducive school climate and the quality of education services. The implication of this study confirms that effective leadership supports sustainable school quality improvement.